2022
DOI: 10.3389/fimmu.2022.841314
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Risk of Liver Fibrosis in People Living With HIV: A Systematic Review and Meta-Analysis

Abstract: ObjectivesIt is unclear if a high level of alcohol consumption is a risk factor for liver fibrosis for people living with HIV (PLWH). This study systematically summarizes the risk relationship between different alcohol consumption and the incidence of liver fibrosis among PLWH.MethodsWe identified potential studies by searching the PubMed, Embase, Web of Science Library, and CNKI databases up to September 26th, 2021. Observation studies in PLWH that evaluated the relationship between alcohol consumption and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…Development of liver fibrosis is a significant clinically-relevant problem in HIV infection, and the risk of progression to end-stage liver disease in PLWH is more prominent in alcohol abusers [ 24 ]. As revealed from our previous studies, the combined treatment of RLW cells with AGS and HIV induced the highest rates of hepatic apoptotic cell death, and these data were confirmed on PHH exposed to HIV and ethanol [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Development of liver fibrosis is a significant clinically-relevant problem in HIV infection, and the risk of progression to end-stage liver disease in PLWH is more prominent in alcohol abusers [ 24 ]. As revealed from our previous studies, the combined treatment of RLW cells with AGS and HIV induced the highest rates of hepatic apoptotic cell death, and these data were confirmed on PHH exposed to HIV and ethanol [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis reported that PLWH drinking > 50 g (6.25 units) of alcohol daily were 3 times more likely to develop hepatic fibrosis. 38 In addition, alcohol use disorder is associated with a 3–7 fold higher risk of liver-related events and liver-related mortality in PLWH. 39,40 Our data suggest that alcohol is a major player contributing to CLD in PLWH and this needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that in a subset of unhealthy alcohol consumption, there is decreased resiliency of intestinal barrier making the host more susceptible to increased intestinal permeability, gut-derived endotoxemia, and end-organ damage. This 2-hit hypothesis might explain why unhealthy alcohol consumption increases the risk of more severe liver disease in patients at risk of other forms of liver disease such as human immunodeficiency virus ( 59 ), viral hepatitis ( 60 ), and metabolic dysfunction–associated steatotic liver disease ( 61 ).…”
Section: Discussionmentioning
confidence: 99%